Pharmacological evaluation of cellular and molecular mechanism of Anti-Inflammatory and Immunomodulatory effects of traditional herbal drug extract of Hedychium spicatum in Experimental Models of Bronchial Asthma - Gulati, Kavita; Sharma, Hemlata; Thokchom, Suresh; Verma, Pankaj; Ray, Arunabha (Asian Journal of Pharmaceutical Research and Development, 2024)
The study assessed the effects of standardized extracts of Hedychium spicatum on airway inflammation and immunomodulatory parameters in experimental model of bronchial asthma in rats. Wistar rats were immunized with ovalbumin (OVA) adsorbed on to aluminium hydroxide (i.p.) and challenged with aerosolized ovalbumin from day 15 to 22. Standardized extracts of Hedychium spicatum were administered orally for 22 days in different treatment groups. After 24h of last challenge, rats were anesthetized and blood and bronchoalveolar lavage fluid (BALF) were collected, centrifuged and analyzed for proinflammatory cytokines TNF-α, NF-κB, Th2 type cytokines IL-4 and cell count.The results showed that eosinophil cells levels were elevated in the immunized rats which were reduced in the treatment group Hedychium spicatum extract as compared to control. These results were comparable with the effects of the standard drug prednisolone. The results showed that extract of Hedychium spicatum has anti-inflammatory and immunomodulatory effects. Thus, the results suggest that the beneficial effects of Hedychium spicatum in bronchial asthma could be due to balancing influence on prooxidant-antioxidant status and reducing the airway inflammation.